NEUTRON REFLECTOMETRY FROM STEREOTAXIC ISOMERS OF POLY(METHYL METHACRYLATE) MONOLAYERS SPREAD AT THE AIR-WATER-INTERFACE - Henderson, J; Richards, R; Penfold, J; Shackleton, C; Thomas, R (1991)
Surface pressure-area isotherms on poly(methyl methacrylate) 'monolayers' spread at the air-water interface show that the isotactic polymer is in good solvent conditions, whereas the atactic and syndiotactic isomers are in thermodynamic environments that are worse than 'theta' conditions. Neutron reflectometry data have been analysed to give monolayer thickness and composition. At low surface concentrations, the layer thickness of the syndiotactic polymer increases to an eventually constant value although the surface pressure and concentration increase still further. For the isotactic polymer, the layer thickness is essentially constant over the range of surface concentrations investigated. Initially, the monolayers contain a considerable volume fraction of air, which decreases as the surface concentration increases. The monolayer thicknesses obtained are considerably larger than recent estimates from ellipsometry measurements, and possible sources for this discrepancy are discussed. © 1991.